The Threnodies of Love: Reading the Maturation Process in Young Adult Love Narratives through a Kristevan Lens; and Messy, a Young Adult Novel - Kugler, Kerstin Maria (Curtin University, 2019)
Drawing on the work of Julia Kristeva and other post-structuralist theorists who extend traditional representations of themes commonly associated with young adult literature, namely the construction of identity, growth and maturation, this thesis, which comprises an exegesis and accompanying young adult novel, seeks to make a meaningful contribution to the high-quality literary output of young adult literature and is intimately linked to Kristeva’s theory on the construction of subjectivity as subjects-in-process within love relationships.